Behavior change techniques in health professional training: developing a coding tool. Issue 1 (10th December 2018) - Pearson, Emma; Byrne-Davis, Lucie; Bull, Eleanor; Hart, Jo
Abstract : An e-tool to identify the 'active ingredients' of education which help to change health workers' practices was developed. Educators can use the tool to understand how Continuing Professional Development (CPD) training changes clinical practice. Abstract: Health professional Continuing Professional Development (CPD) courses often aim to change practice; understanding which training techniques drive behavior change can help educators facilitate this. The 93-item Behaviour Change Technique Taxonomy (BCTT) describes behavior change techniques (BCTs) used in behavior change interventions but was not designed for understanding CPD; it is necessary to explore how best to use the BCTT in this context. This study aimed to explore the BCTs used by CPD course educators to change healthcare practice and to develop and pilot an e-tool, based on the BCTT, to enable course designers and educators to understand which BCTs are in their training. This understanding could lead to enhanced CPD and an experimental approach to assessing the benefits of including a variety of BCTs in CPD. Two psychologists, trained in using the BCTT, observed three postgraduate medical CPD courses. In Phase 1, the BCTT was used to code 26 hours of observations. An e-tool including observed BCTs was developed and used to code 35 hours of observations in Phase 2. Feedback was collected through short discussions with educators from each course. The tool was further refined in Phase 3. Thirty-seven BCTs were identified in Phase 1, a further four in Phase 2, and a further two in Phase 3. The final e-tool comprised 43 BCTs with examples of their use based on course observations to aid identification, since educators fed back that they would value an uncomplicated tool with practice-related examples. A coding tool to understand the active ingredients in health professional CPD could enable educators to maximize the impact of CPD on practice. Further work should explore whether educators themselves are able to use the tool to code their training interventions.